The use of alternative fuels for maritime decarbonization: Special marine environmental risks and solutions from an international law perspective - Wang, Qiuwen; Zhang, Hu; Huang, Jiabei; Zhang, Pengfei (Frontiers in Marine Science, 2023)
The introduction of several alternative marine fuels is considered an important strategy for maritime decarbonization. These alternative marine fuels include liquefied natural gas (LNG), liquefied biogas (LBG), hydrogen, ammonia, methanol, ethanol, hydrotreated vegetable oil (HVO), etc. In some studies, nuclear power and electricity are also included in the scope of alternative fuels for merchant ships. However, the operation of alternative-fuel-powered ships has some special risks, such as fuel spills, vapor dispersion and fuel pool fires. The existing international legal framework does not address these risks sufficiently. This research adopts the method of legal analysis to examine the existing international legal regime for regulating the development of alternative-fuel-powered ships. From a critical perspective, it evaluates and predicts the consequences of these policies together with their shortcomings. Also, this research explores the potential solutions and countermeasures that might be feasible to deal with the special marine environmental risks posed by alternative-fuel-powered ships in the future.